How to Implement and Supervise a Learning Style Program. - Dunn, Rita (ASCD, 1996)
This how-to book is for supervisors interested in understanding, implementing, and guiding staff in the proven educational methods of learning styles. Learning how to learn is what the learning styles approach is all about. Advocate Rita Dunn explains learning styles and how they develop and describes how to teach students with diverse learning styles. International studies and testimonials indicate statistically higher standardized achievement test scores for students who are taught to use their learning style strengths and yield evidence that this approach makes a difference for all kinds of.